Representaciones sociales del docente en formación en torno a la práctica pedagógica: reflexiones a los hallazgos develados - María Lucila Velazco-Valderrama; Ana Lourdes Laguado-Oicatá; Félix Joaquín Lozano-Cárdenas Lozano-Cárdenas (Mundo Fesc)
This article arises with the purpose of disseminating the reflections around the stories and conclusions of a scientific investigation that aimed to reveal the social representations that underlie students of the Bachelor of Education on pedagogical practice in rural contexts. The study was framed in the qualitative approach supported by the grounded theory analysis method in order to configure an ontological, epistemic and methodological vision applied to twelve subjects (12) students, taking part in professional practice in educational institutions of Primary Basic of the Municipality Junín, Táchira Venezuela. Vision that is specified with Moscovici's Theory of Social Representations to interpret the dynamics that surround pedagogical action from the meanings, beliefs, and experiences of these participants. The findings revealed and the conclusions constructed were nuanced from the conceptual elements of this theory (field of representation, field of information and attitude).